Posters for peace : visual rhetoric & civic action - Benson, Thomas W. (The Pennsylvania State University Press, 2015)
"Posters for Peace is a book about a collection of posters made and circulated on and about the campus of the University of California, Berkeley. In May 1970, as part of a national wave of protests against the Vietnam War, an invasion of Cambodia, and the killing of four students at Kent State University, groups of students at Berkeley produced and distributed a series of political posters. This book presents a rhetorical history and criticism, as well as a catalogue of a collection of some of the recovered posters, which are part of the Thomas W. Benson Political Protest Collection at the Penn State University Libraries"--Preface.